(untitled) (Hematology Meeting Reports, 2009)
Clinically significant hemorrhage, especially intracranial hemorrhage, is a major cause of morbidity and mortality in extremely preterm infants and is a rare event in otherwise healthy term infants. Infusions of FFP in newborn infants is effective in reducing blood loss associated with extracorporeal membrane oxygenation or cardiopulmonary bypass and to treat active bleeding due to disseminated intravascular coagulation, liver failure or vitamin K deficiency. However, routine use of fresh frozen plasma (FFP) in sick preterm infants for volume expansion, to treat coagulopathy in the absence of bleeding, or for partial exchange transfusion does not decrease mortality or morbidity.